Evaluation of Meloidogyne incognita and Rotylenchulus reniformis nematode-resistant cotton cultivars with supplemental Corteva Agriscience nematicides - Kate Turner, A.; Graham, Scott H.; Potnis, Neha; Brown, Steve M.; Donald, Pat; Lawrence, Kathy S. (Journal of nematology, 2023)
- and -resistant new cotton cultivars have recently become available, giving growers a new option in nematode management. The objectives of this study were: (i) to determine the yield potential of the new cultivars PHY 360 W3FE ( -resistant) and PHY 332 W3FE ( -resistant) in nematode-infested fields and (ii) to evaluate the effects of combining the nematicides Reklemel (fluazaindolizine), Vydate C-LV (oxamyl), and the seed treatment BIO Nematicide 100 (heat killed and its non-living spent fermentation media) with resistant cotton cultivars on nematode population levels and lint yield. Field experiments in 2020 and 2021 indicated population levels were 73% lower on PHY 360 W3FE (R) and 80% lower for on the PHY 332 W3FE (R) at 40 days after planting. Nematode eggs per gram of root were further reduced an average of 86% after the addition of Reklemel and Vydate C-LV when averaging both cultivars over the two years. Tests with BIO Nematicide 100 + Reklemel + Vydate C-LV (0.56 + 2.5 L/ha) in both and fields produced higher lint yields. Overall, planting PHY 360 W3FE (R) and PHY 332 W3FE (R) improved yields an average of 364 kg/ha while limiting nematode population increases. The addition of the nematicides further increased yields 152 kg/ha of the nematode-resistant cultivars.